23 The sads heart of the matter: a review of the sudden arrhythmic death syndrome (SADS) biobank in the mater misericordiae university hospital; the cornerstone of a national strategy. (16th October 2019) - Carron, J; McGorrian, C; Haverin, K; Gallagher, M; Fitzgibbon, M; O' Brien, J; Galvin, J; Fabre, A
Abstract : Background: Sudden cardiac death (SCD) is a devastating event for a family and the wider community. While coronary artery disease is the primary culprit in an older population, SCD in a young cohort (age 1–35) is more commonly attributed to structural and arrhythmogenic syndromes, for which there is often an underlying genetic basis. An estimated 10, 000 people in Ireland carry gene mutations for inherited cardiac conditions (ICC), with one young person dying suddenly each week from such syndromes according to the SCD registry. Aim: To review detection rates of genetic variants in samples tested via the SADS BioBank following SCD in a young person and possibly demonstrate the merits of such a resource in terms of primary prevention for family members. Methods: Family review and consent for genetic testing was carried out in the Family Heart Screening Clinic (FHSC). Retrospective analysis of results of samples sent for molecular autopsy via the SADS BioBank from its induction in January 2015 was performed. Detection rates of causative gene variants and the number of family members diagnosed with an ICC was also reviewed. All genetic analysis was conducted via the same internationally validated next generation sequencing lab. Results: From January 2015 to March 2019, 145 samples had been stored in the SADS BioBank; 48 (33%) female and 97 (67%) male. Of these, 21 (14.5%) samples (13 male, 8 female, age 13–56) were sent for genetic testing: 19 for a full inherited cardiovascular disease panel consisting of a 380 gene molecular autopsy and 2 for a targeted hypertrophic cardiomyopathy (HCM) panel (173 genes). Of the 21 samples tested, 9 (43%) were positive for genetic variants (figure 1 ): 4 were American College of Medical Genetics (ACMG) Class IV or V mutations considered to be pathogenic, and 5 were ACMG class III variants of uncertain significance (VUS) i.e variants not previously reported in the literature as disease causing. Familial cascade screening following confirmation of a pathogenic mutation in the proband resulted in detection of 3 (33.3%) positive genotypes in 9 first-degree relatives tested. Clinical screening of relatives of the probands who displayed a VUS resulted in 5 ICC diagnoses in 19 (26%) first-degree relatives (table 1 ). Despite negative gene testing in 12 of the SCD probands, 4 of 42 (9.5%) first-degree relatives were given an ICC diagnosis following clinical screening in the FHSC. Conclusions: This short study demonstrates the unique potential the SADS BioBank has to offer in terms of identifying those most at risk and optimising prevention strategies for family members, while also forming a genetic profile of SCD due to ICC in Ireland. Notably, definite or possible pathogenic variants were identified in almost half of samples studied. It highlights that a large proportion of families affected by SADS are overlooked by this crucial screening opportunity. Genetic testing following a SADS death relies on referral of the family to appropriate specialist screening centers. Increased awareness of the current pathway is pivotal if this asset is to be optimally utilised and these potentially lethal cardiac conditions identified in time.